Repair of Bilateral Quadriceps Tendon Rupture Using a Modified Knotless Suture Anchor and Internal Brace Technique: Surgical Technique and Case Report - Xiaoping Wang; Daoqiang Huang; Weili Feng; Weiwei Wu; Jian Huang; Luyao Chen; Yumin Tu (Orthopaedic Surgery, 2022)
Background Quadriceps tendon rupture (QTR) is a rare clinical condition often caused by indirect injury in healthy people. In addition, spontaneous and bilateral ruptures can occur in patients with predisposing factors, such as endocrine or rheumatic disease. Currently, several QTR repair techniques have been proposed; however, no consensus exists about the best repair technique. Case Presentations A 55‐year‐old man with renal failure secondary to glomerulonephritis suffered from spontaneous bilateral quadriceps tendon ruptures. Based on a knotless suture anchor and internal brace, a novel double‐row suture‐bridge configuration surgical approach was used to treat the patient. At 11‐month follow‐up, the patient maintained excellent function, with a Lysholm score of 91 for both knees. Conclusions This technique may be an effective method for repairing ruptured quadriceps tendons.